Cardioprotective effect of Sanguisorba minor against isoprenaline-induced myocardial infarction in rats - Hosseini, Azar; Ghorbani, Atieh; Alavi, Mohaddeseh Sadat; Forouhi, Nima; Rajabian, Arezoo; Boroumand-Noughabi, Samaneh; Sahebkar, Amirhossein; Eid, Ali H. (Frontiers in Pharmacology, 2023)
Introduction: Oxidative stress is a major instigator of various cardiovascular diseases, including myocardial infarction (MI). Despite available drugs, there is still an increased need to look for alternative therapies or identify new bioactive compounds. Sanguisorba minor (S. minor) is a native herb characterized by its potent antioxidant activity. This study was designed to evaluate the effect of S. minor against isoprenaline-induced MI. Methods: Rats were treated with the hydro-ethanolic extract of the aerial parts of S. minor at doses of 100 or 300 mg/kg orally for 9 days. Isoprenaline was injected subcutaneously at the dose of 85 mg/kg on days 8 and 9. Then, the activities of various cardiac injury markers including cardiac troponin (cTnT), lactate dehydrogenase (LDH), creatinine kinase muscle brain (CK-MB), creatinine phosphokinase (CPK), and antioxidant enzymes in serum were determined. Malondialdehyde (MDA) and thiol content were measured in cardiac tissue, and histopathological analysis was conducted. Results: Our results show that isoprenaline increased the serum levels of cTnT, LDH, CK-MB, and CPK (p < 0.001) and elevated MDA levels (p < 0.001) in cardiac tissue. Isoprenaline also reduced superoxide dismutase (SOD), catalase, and thiol content (p < 0.001). Importantly, the extract abolished isoprenaline-induced MI by elevating SOD and catalase (p < 0.001), reducing levels of MDA, and diminishing levels of cTnT, LDH, CK-MB, and CPK cardiac markers (p < 0.001). Histopathological studies of the cardiac tissue showed isoprenaline-induced injury that was significantly attenuated by the extract. Conclusion: Our results suggest that S. minor could abrogate isoprenaline-induced cardiac toxicity due to its ability to mitigate oxidative stress.